Dual‐metal single‐atomic catalyst: The challenge in synthesis, characterization, and mechanistic investigation for electrocatalysis. Issue 4 (2nd February 2022) - Chen, Changli; Sun, Mengru; Wang, Kaixuan; Li, Yujing
Abstract: Dual‐metal single‐atom catalysts (DACs), featuring high atomic utilization efficiency, excellent selectivity, and stability originating from the atomically dispersed nature, have emerged as a new frontier in heterogeneous electrocatalysis due to the synergistic effect between diversified metal active sites in promoting their catalytic activity. In this review, the recent progress and development on the syntheses, characterizations, theoretical uniqueness, and applications for various catalytic reactions and devices (oxygen reduction reaction, oxygen evolution reaction, hydrogen evolution reaction, CO2 reduction reaction, N2 reduction reaction, proton exchange membrane fuel cells) are summarized and reviewed. Specifically, the synergistic effect between the two metal centers and electronic structures of catalysts is systematically discussed. Moreover, the future challenges and prospects in developing practical DACs are proposed as a possible direction for further investigation. Abstract : Dual‐metal single‐atom catalysts (DACs), featuring high atomic utilization efficiency, excellent selectivity, and stability originating from the atomically dispersed nature, have emerged as a new frontier in heterogeneous electrocatalysis due to the synergistic effect between diversified metal active sites in promoting their catalytic activity. As the investigation on DACs is still in the early stage, it is possible to summarize the design, preparation, characterization, theoretical calculation and prediction, and application of DACs for electrocatalysis.